SISTEM KETERTELUSURAN ELEKTRONIK UNTUK PENGUATAN PERTANIAN ORGANIK PARTICIPATORY GUARANTEE SYSTEM [ELECTRONIC TRACEABILITY SYSTEM FOR STRENGTHENING ORGANIC FARMING PARTICIPATORY GUARANTEE SYSTEM] - Priantoro, Akhmad Unggul; Prihartono, Agung; Dragon, Bullion (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2024)
The Participatory Guarantee System (PGS) is a community-based effort to ensure the quality of organic agriculture produces, supporting organic farmers as an alternative to organic certification by Organic Certification Bodies (LSO), which is very expensive and time-consuming. PGS is an internationally recognized practice by IFOAM (International Federation of Organic Agriculture Movements) to provide quality assurance to consumers of organic agricultural produces. In practice, PGS relies on manual record-keeping and trust among the community members, with no strict sanctions against fraudulent activities. This makes PGS vulnerable to deviations that could harm all stakeholders. Therefore, an effective and efficient electronic traceability system is needed to support the development of PGS-based organic agriculture. This study proposes a design for an electronic traceability system that meets the needs of PGS.